SDF-1/CXCR4 Axis Promotes MSCs to Repair Liver Injury Partially through Trans-Differentiation and Fusion with Hepatocytes - Ning-Bo Hao; Chang-Zhu Li; Mu-Han Lü; Bo Tang; Su-Min Wang; Yu-Yun Wu; Guang-Ping Liang; Shi-Ming Yang (Stem Cells International)
MSCs have become a popular target for developing end-stage liver therapies. In this study, two models of bone marrow chimeric mice were used to construct the liver failure models. Then it was found that MSCs can transdifferentiate into hepatocyte-like cells and these hepatocyte-like cells can significantly express albumin. Furthermore it was also found that MSCs can fuse with the hepatocytes and these cells had the proliferation activity. However, the percentage of transdifferentiation was significantly higher than fusion. So it was considered that MSCs which transdifferentiated into hepatocyte-likes cells played important roles for repairing the injuring liver function.